Questioning the Distraction of Imam Shafi'I's Absence in the Reports of Bukhari and Muslim - Saputra, Muhamad Rama; al Ayubi, Sholahuddin; Alif, Muhammad (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2023)
This paper is about Imam Shaykhon (Bukhari and Muslim) leaving out a narration from Imam Shafi'i. A thing that is left out is certainly not free from causes and intentions. If a narration is left out of a hadith, there must be some shadz and illat in the hadith or the person who reported it. Then, is Imam Shafi'I unjust and has many shadz and illat. From the statements of the scholars about Imam Shafi'I, that he is a Hadith expert. Imam Ahmad bin Hanbal stated that if it were not for Shafi'I, I would not know hadith. This library research relies on library research materials, such as books, books, journals, encyclopedias, and magazines, as data sources to search and track these issues. From the findings of this research, that leaving the history of Imam Shafi'I has a purpose and a veil. Leaving his narration does not mean that there is an illat, but it shows praise and honor towards Imam Shafi'I.